Veränderliche 3D Zellgerüstträger auf Cryogelbasis zur Kultivierung von Prostatakarzinomzellen - Bäcker, Anne (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2017)
In this work, three-dimensional (3D) cell scaffolds based on cryogels of different polymers were developed and subsequently used for the cultivation of prostate carcinoma cells. Moreover, different scaffolds on the basis of the silk protein, fibroin, were synthesized and also served as cultivation environment for established prostate cancer cells.